RANCANG BANGUN PENGONTROL MODUL GSM SIM300C BERBASIS MIKROKONTROLER PIC 18F452 - Surya Alimsyah; Lin Prasetyani (Technologic, 2012)
GSM is rife of communication used today. The information carried in the GSM communications can be both call (telephone) and messages (SMS). In this final project has been prepared using a remote-controlled by means of SMS GSM communications. Information messages on the GSM communication is better known as SMS can be integrated with the performance of the microcontroller to control the output relay. In designing, a PIC 18F452 microcontroller is used to control the on-off of eight outputs are connected to the output relays. Control commands will be sent via SMS by the recognized telephone number through the mobile phone controller will communicate with GSM module SIM300C. In addition to controlling the PIC-controlled commands to perform checks on the overall condition of the output on the Input / Output modules.